MENINGKATKAN KETERAMPILAN MENULIS PARAGRAF MELALUI PENERAPAN MODEL PEMBELAJARAN CONCEPT SENTENCE DENGAN PERMAINAN DETECTIVE SHERLOCK HOLMES AND THE ADVENTURE BOOK - Fajriani, Rizky; Djuanda, Dadan; Sudin, Ali (Jurnal Pena Ilmiah, 2017)
Â This research was conducted as an effort to improve the quality of process and learning result from paragraph writing skill of Indonesian subject in SDN Wargaluyu Kecamatan Ganeas Kabupaten Sumedang through the application of Model Concept Sentence with the game Sherlock Holmes and The Adventure Book. The result of observation and the interview on the initial data indicated that present the problem with the writing competence of student. Based on the problem which is found on the learning process, then the selected method in this research is class action research with Kemmis and Mc Taggart design. Over all, the improvement ofprocess and the result learning occured in three times cycle. The collecting data for research importance was conducted through observation technique, interview, test, and field record. All data which has been found were validated with member check, triangulation, audit trail and expert opinion.Â The result of processing data showed that model Concept Sentence with game Sherlock Holmes and The Adventure Book are able to improve the process and the learing result from paragraph writing skill of third grade students of SDN Wargaluyu.Â